Beyond anaphylaxis: acute myocardial infarction with ischemic stroke after bee sting a case report - Zainab Mehdi; Monica Gupta; Anish Garg; Narinder Kaur (طب اورژانس ایران, 2023)
Although Hymenoptera stings mostly present with benign local inflammation, they can also be fatal. The true incidence of fatal reactions is unknown as sudden deaths due to insect bites might be regarded as heart attacks or strokes. Hymenoptera stings remain an underrecognized and underdiagnosed entity with no relation between the early cutaneous manifestations and the uncommon deadly reactions that are seen days to weeks later. We report a case of a 69-year-old farmer referred to our hospital with both acute coronary syndrome and acute ischemic stroke approximately 5 hours after a bee sting without a history of any initial anaphylaxis.